Silane-Modified Graphene Oxide Composite as a Promising Corrosion-Inhibiting Film for Magnesium Alloy AZ31 - Zhang, You; Wang, Juping; Zhang, Zheng; Wei, Kai; Zhang, Zhe; Hao, Xuelong; Chen, Fei (Frontiers in Materials, 2021)
In this study, (3-aminopropyl)-triethoxysilane–modified graphene oxide (GO) composite thin films were synthesized on magnesium alloy AZ31 substrate. The structure, composition, and morphology of silane-GO films were analyzed. Electrochemical measurements and immersion tests showed that silane-GO coatings provide effective protection for magnesium alloy substrates, owing to the good barrier property of the layered GO, and decrease the defects on the GO film surface due to the silane modification. In addition, the corrosion product between the outer silane-GO film and Mg alloy substrate also improved the corrosion resistance of the Mg alloy. Thus, silane-GO composite thin films provide an effective approach for protecting the lightweight metal substrate.